The Impact of Antibiotic Use on Immune Function and Gut Microbiota in Children Aged 1–5 Years - Putri, Ranita Ema; Anisa, Fitri (International Journal on ObGyn and Health Sciences, 2024)
The use of antibiotics in young children has been linked to disruptions in gut microbiota and immune function, potentially leading to increased susceptibility to infections, allergies, and autoimmune conditions. This study aims to analyze the effects of antibiotics on the immunity of children aged 1–5 years, examining variations based on age, gender, and type of antibiotic used. A longitudinal cohort study was conducted involving 300 children aged 1–5 years. Participants' gut microbiota and immune parameters were assessed at baseline and monitored over a two-year period, with follow-up evaluations every six months. Data on antibiotic use, infections, allergic reactions, and autoimmune conditions were collected through parental reporting and medical records. Microbiota composition was analyzed using next-generation sequencing, and immune function was assessed via blood tests measuring T cells, B cells, and immunoglobulin levels. Antibiotic use led to significant reductions in gut microbiota diversity and altered immune cell populations, with younger children (1–2 years) experiencing more pronounced disruptions. Boys exhibited slightly higher sensitivity to these effects compared to girls. Broad-spectrum antibiotics caused more severe and prolonged microbiota and immune function disruptions than narrow-spectrum antibiotics. Children with frequent antibiotic exposure showed higher rates of respiratory and gastrointestinal infections, as well as increased prevalence of allergic diseases and autoimmune conditions. Further research is needed to explore the long-term impacts and underlying mechanisms of antibiotic-induced immune changes.